(untitled) (Research, Society and Development, 2020)
This article aims to reflect on the evolutionary human anatomy teaching and the insertion of new technologies of teaching and learning in medical training. It is a reflective theoretical study. The search and analysis of the bibliographic framework used occurred through a narrative review of the literature. The organization of the results was made through Context Analysis. The contexts used were: New technologies in teaching anatomy as immediate context; Current perspectives in medical education as a specific context; Legislation and ethics in the use of cadavers as a general context; and Historical evolution of the study of anatomy as a meta-context. The competences expected by medical students who have undergone continuous training in human anatomy using different methodologies. Even so, the importance as well as the ethical aspects involved in the use of cadavers is emphasized.